PENGARUH ORIENTASI KEAGAMAAN POLITIK-TEOLOGIS TERHADAP SIKAP TOLERANSI SISWA MUSLIM SMA DI PURWOKERTO (Studi Kasus di SMA N 1 Purwokerto, SMA IT Al Irsyad Purwokerto, SMA Muhammadiyah 1 Purwokerto dan SMA Diponegoro 1 Purwokerto) - , WIWIT KURNIAWAN, Mohammad Iqbal Ahnaf, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of this research are to reveal how the political and theological religious orientation of students, and the level of tolerance attitude. Moreover, it would also analyze the relationship between theological and political orientation towards religious tolerance level. This study is located at the four schools in Purwokerto, namely SMAN 1 Purwokerto, SMA IT Al Irsyad Purwokerto, SMA Muhammadiyah 1 Purwokerto, and SMA Diponegoro 1 Purwokerto. This study uses quantitative methods and using a questionnaire as a means to obtain the data. Research shows that the Puritan and substansialist categories are dominant orientation in students. As well as the, religious theological orientation has an influence on the level of religious tolerance while political orientation has no effect on tolerance.